The epizootic situation of bovine paratuberculosis in Ukraine for the period 2019–2023 - A. V. Pyskun; O. D. Polishchuk; O. L. Kravtsova; L. Y. Korniienko; V. V. Ukhovskyi; H. M. Mietolapova; O. V. Pishchanskyi; G. B. Aliekseieva (Regulatory Mechanisms in Biosystems, 2024)
Paratuberculosis (Johne’s disease) is a contagious infectious disease, the etiological agent of which affects various species of mammals, mainly ruminants. The causative agent is the acid-resistant bacterium Mycobacterium avium subsp. paratuberculosis (MAP), which belongs to the family Mycobacteriaceae. The most sensitive to it are domestic ruminants (cattle, sheep, goats etc.), which are the main reservoirs of infection for the various species of animals and humans (the zoonotic potential of the pathogen requires further study). In Ukraine, the main methods for diagnosing paratuberculosis are serological and bacteriological techniques. The authors analyzed the epizootic situation of paratuberculosis among cattle in Ukraine during 2019–2023 by systematizing the data of their own research and official reports of state veterinary laboratories in regions. The results of the investigation are presented without taking into account the temporarily occupied territories of Luhansk and Donetsk oblasts and the Autonomous Republic of Crimea, as well as part of the territory where military operations were conducted. In total, over the five-year period, 41 679 samples were examined serologically in the complement fixation test and 13 405 – bacteriologically, by microscopy and cultivation of biological materials on the nutrient media. During the investigation, specific antibodies to the pathogen were detected in 36 samples (prevalence, about 0.1%; BCI, 0.06–0.12%) from the ten regions. The analysis of the serological studies shows that the disease is sporadic and has a significant downward trend in the number of positive cases (17 positive samples were detected in 2019 and 2020, and only two in 2023). As for bacteriological examination, no positive cases have been registered during the 5-year period. In addition to the scrupulous work of the veterinary medicine service, both the persistent decrease in the cattle population and the ongoing hostilities in Ukraine have a considerable impact on improving the epizootic situation., as the number of serological tests conducted after 2022 has almost halved (especially in the eastern and southern regions), and bacteriological tests have decreased fivefold. The visualization of the data shows that antibodies were mostly detected in animals from the central, eastern, northern, and northwestern regions of the country.